The Differences Of Doctor Adherence And Medical Record Completeness In Accredited And Unaccredited Primary Health Care - Aisyah Shofiatun Nisa (Universitas Muhammadiyah Yogyakarta, 2018)
In the field of medical and dentistry, medical records is one of authentic evidence a service provided by doctor and dentist, which contain clinical record of a patient. Accreditation is one of method made by government to control and maintain the quality of public health service. The purpose of this study is to analyze the differences in the completeness medical records at primary health care that have been accredited and haven’t. Quantitative descriptive method which observes the field condition is used in this research. Approximately the knowledge of a doctor on accredited Primary Health Care is 69.4% while 65.27% for unaccredited Primary health care. As for the assessment for adherence a doctor on accredited Primary Health Care is 87.64% while 73.52% for unaccredited. The completeness medical records from (n: 300 medical records at 6 Primary health care) accredited Primary health care is on 80.33% while unaccredited Primary health care is on 68%. Based on the analysis using paired t-test to assess the differences between the completeness medical records at accredited and unaccredited Primary health care obtained sig value 0.0001. There is a difference in the completeness the medical record between accredited Primary health care and unaccredited Primary health care.